Mucous dilution activity of non soluble ethylacetate fraction syrup of hibiscus flowers (Hibiscus rosa-sinensis L.) at cow intestinein vitro - Mimiek Murrukmihadi; Subagus Wahyuono; Marchaban .; Sudibyo Martono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Previous study indicated that ethylacetate insoluble fraction of ethanol extract of Hibiscus flowers (Hibiscus rosa-sinensis L.) were able to dilute intestine cattle mucous in vitrothat was often associated with mucolytic activity.In this study, syrup preparation of various concentrations of these fractions (1.20, 1.60 and 2.00%) was tested for its ability to dilute of mucous. Each of syrup concentrations was mixed with 20% buffer Phosphate (pH, 7) at equalproportion (1:1 v/v), the resulting mixtures were tested for their ability to dilute mucous in vitro. Mucous dilution was observed by flow time recorded in the viscosimeter. The study showed that all syrup concentrations (1.20, 1.60, 2.00%) exhibited mucous dilution effect compared tonegative control and syrup concentration at 2.00% was comparable to positive control acetylsistein 0.1% (p<0.05). Therefore, there was a possibility that thispreparation could be used as mucolytic.Keywords: Hibiscus rosa-sinensisL., viscosity, mucous dilution, mucolytic